Effects of aromatase inhibitor therapy on visceral adipose tissue area and cardiometabolic health in postmenopausal women with early and locally advanced breast cancer. (1st November 2022) - Cheung, Yee‐Ming M.; Hoermann, Rudolf; Van, Karen; Wu, Damian; Healy, Jenny; Chao, Michael; White, Shane; Yeo, Belinda; Zajac, Jeffrey; Grossmann, Mathis
Abstract: Objective: Aromatase inhibitor (AI) therapy provides oncological benefits in postmenopausal women with oestrogen receptor‐positive breast cancer. However, AI treatment has been associated with increased cardiovascular risk. In nonbreast cancer populations, experimentally induced low oestrogen states and natural transition to menopause have been associated with increases in visceral adipose tissue (VAT), a known surrogate marker for cardiometabolic risk. Given that AI treatment blocks oestradiol production, we hypothesized that AI treatment would increase VAT. Methods: We conducted a prospective 12‐month cohort study of 52 postmenopausal women newly initiating AI treatment (median age: 64.5 years) and 52 women with breast pathology not requiring endocrine therapy (median age: 63.5 years). VAT area and other body composition parameters were measured at baseline, 6 months and 12 months using dual X‐ray absorptiometry. Other risk markers of cardiometabolic health were also assessed. Results: In women initiating AI treatment, there was no statistically significant difference in VAT area after 12 months when compared to controls, with a mean adjusted difference of −5.00 cm 2 (−16.9, 6.91), p  = .55. Moreover, changes in total fat mass, lean mass, subcutaneous adipose tissue area, hepatic steatosis and measures in endothelial function were also not statistically different between groups after 12 months. Findings were similar after adjustments for activity levels and coronavirus disease 2019 lockdown duration. Conclusions: These data provide reassurance that over the initial 12 months of AI therapy, AI treatment is not associated with metabolically adverse changes in body composition, hepatic steatosis or vascular reactivity. The impact of extended AI therapy on cardiometabolic health requires further study.